Group portrait of the Imperial Royal Lion Monarchy (IRLM) Board of Directors, 1994 - Sahl, Ted (photographer):::Creator::::::::::::
Group portrait of the Imperial Royal Lion Monarchy (IRLM) Board of Directors, 1994. From left to right: Mike Allen, Patrick Mayberry, Allen Little, Michael Chadderton, Jerry Beaulieu and Rita.